Macro photography photo workshop - Kamps, Haje Jan (Photo workshop., 2007)
"Macro, or close-up, photography is gaining popularity, and this book covers all of the challenges associated with taking great close-ups: depth of field, focus, and exposure. Co-published with Photoworkshop.com, a leading online educational resource for both beginning and professional photographers, this task-oriented reference allows readers to learn by doing and offers outstanding examples and instructions"--Resource description page.